Effects of Selected Diazotrophs on Maize Growth - Kifle, Medhin H.; Laing, Mark D. (Frontiers in Plant Science, 2016)
Laboratory, greenhouse, and field experiments were conducted at the University of KwaZulu-Natal, Pietermaritzburg, South Africa in the 2010/2011 and 2011\2012 seasons to study the effects of eight strains of diazotrophic bacteria on the growth and yield of maize. Maize seeds were treated with Bacillus megaterium (V16), Pseudomonas sp. (StB5, A3, A6, and A61), Burkholderia ambifaria (V9), Enterobacter cloacae (L1) and Pantoea ananatis (LB5), aiming to stimulate plant growth, and maintain or increase yields while reducing the need for N fertilization. All the diazotrophic bacteria increased germination of maize seed, and Pseudomonas sp. (StB5) and B. megaterium (V16) significantly increased shoot length. Pseudomonas sp. (StB5), B. megaterium (V16), E. cloacae (L1), B. ambifaria (V9) and Pseudomonas sp. (A3) very significantly increased root length and seed vigor index. Under greenhouse conditions, plants treated with diazotrophic bacteria developed more leaf chlorophyll and greater dry weight, albeit not significantly (n.s.). In a field trial in 2010/2011, application of the best five diazotrophic bacteria, with or without 33% N-fertilizer, had no significant effect on germination, grain yield, dry weight, plant height and leaf chlorophyll. In the 2011/2012 growing season, at 60 days after planting (DAP), all the diazotrophic bacteria increased plant dry weights to equal that of the fertilized control (33%N-fertilizer)(n.s.). After inoculation with the diazotrophs alone increased plant heights (n.s.), and chlorophyll contents (n.s.). With the addition of 33%N-fertilizer at planting, the diazotrophs still caused increases of chlorophyll content relative to the control with 33%N (n.s.). It may be concluded that the tested diazotrophs alone may be beneficial for use on maize growth.